2021
DOI: 10.1073/pnas.2108157118
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-elicited CD4 T cells prevent the deletion of antiviral B cells in chronic infection

Abstract: Chronic viral infections subvert protective B cell immunity. An early type I interferon (IFN-I)–driven bias to short-lived plasmablast differentiation leads to clonal deletion, so-called “decimation,” of antiviral memory B cells. Therefore, prophylactic countermeasures against decimation remain an unmet need. We show that vaccination-induced CD4 T cells prevented the decimation of naïve and memory B cells in chronically lymphocytic choriomeningitis virus (LCMV)-infected mice. Although these B cell responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…6 M ). We and others have reported that LCMV-specific B cells undergo biased terminal differentiation into short-lived antibody-secreting cells, when triggered in the first 3 d after infection ( 79 , 82 84 ). This process is driven by IFN-I-driven inflammation and results in a substantial depletion of virus-specific B cells, termed “B cell decimation”.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…6 M ). We and others have reported that LCMV-specific B cells undergo biased terminal differentiation into short-lived antibody-secreting cells, when triggered in the first 3 d after infection ( 79 , 82 84 ). This process is driven by IFN-I-driven inflammation and results in a substantial depletion of virus-specific B cells, termed “B cell decimation”.…”
Section: Resultsmentioning
confidence: 95%
“…We extended our assessment of KL25 BCR-expressing B cells in antiviral immune responses and included also the more commonly used KL25HL strain ( 79 , 82 84 ) as a B cell donor. KL25HL mice carry the KL25H knock-in allele in conjunction with a transgenic KL25 light chain, thus a similar genetic configuration as the independently generated BasL36 strain, but B cells of KL25HL mice bound GP1 at lower levels and less consistently than BasL36 B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed heterogeneity in the distribution of transcription factors within exhausted T cells undergoing oxidative stress-induced cell death. The antigen-presenting function of B cells in the cellular immune process is crucial, despite their classification as nonclassical antigen-presenting cells 74 . We found that the B_CD74 subgroup, which possesses antigen-presenting ability, accounted for up to 20% (maximum proportion) of lymphocytes in the NPD-pre group, but was completely absent in the PD-pre group.…”
Section: Discussionmentioning
confidence: 99%
“…When mice were exposed to S antigen after vaccination, CoVAX_MNS-induced CD4 + T cells accelerated the generation of class-switched IgG Abs specific for the incoming S. In vitro, these CD4 + T cells upregulated CD40L and produced TNF upon S peptide stimulation, demonstrating that vaccination elicited S-specific T helper type 1 (T H 1) cells, which explains class switching to IgG2c. The most likely scenario is that upon encountering the S, the S-specific CD4 + T cells, including T H 1 and, potentially, T follicular helper cells, are recruited to lymph nodes and promote a germinal center response, which involves interaction with naive, S-specific B cells to promote their activation and differentiation into Ab-secreting plasmablasts ( 73 ). Similarly, CoVAX_MNS-vaccinated mice exposed to full-length S had accelerated generation of CD8 + T cells specific for an S epitope not contained within the vaccine.…”
Section: Discussionmentioning
confidence: 99%